The HBM4EU chromates study – Outcomes and impacts on EU policies and occupational health practices - Santonen, Tiina (2023)
Funding Information: The recently completed EU human biomonitoring initiative (HBM4EU, www.hbm4eu.eu/about-hbm4eu/), was a European Joint Programme that aimed to harmonise the collection and use of biomonitoring data to better understand human exposure to chemicals in the environment, in occupational settings and through the use of consumer products to improve chemical risk assessment and management efforts, and to support policy making (Ganzleben et al., 2017). Within the context of the HBM4EU project several priority substances were selected for investigation based on the most important needs of policy makers and risk assessors, as well as common needs of participating countries and a broad range of other stakeholders including trade unions (Ougier et al., 2021). Many of the priority substances, along with having an important economic role, also pose health risks for workers due to their occupational use. One of the priority substances was hexavalent chromium (Cr(VI)), which was the main focus of the first of a series of three different HBM4EU occupational studies (Santonen et al. 2019a, 2022), the other two being focussed on electronic waste (E-waste) and diisocyanates exposures (Jones et al., 2022; Scheepers et al., 2021). In addition to Cr(VI), it was recognised that in chrome plating activities there may also be exposure to another group of HBM4EU priority chemicals, per- and polyfluoroalkyl substances (PFASs). PFASs, including PFOS (perfluorooctane sulfonate), have been used as mist suppressants in chrome plating baths to prevent the evaporation of Cr(VI) vapours (Blepp et al., 2017; Gluge et al., 2020). Although PFOS has now been largely replaced in the EU, many of its substitutes in chrome plating activities are also PFASs which may cause similar health and environmental concerns.Occupational exposure to Cr(VI) has been associated with an increased risk of lung and sinonasal cancers and is suspected to lead to gastrointestinal tract cancers (den Braver-Sewradj et al., 2021; ECHA 2013; IARC 2012). In addition, it is a common cause of occupational asthma, allergic dermatitis and there is a concern for adverse effects on reproductive health (Sun and Costa 2022). Exposure to Cr(VI) may occur in several occupational activities, e.g., in welding, Cr(VI) electroplating and other surface treatment processes such as paint application and removal of old paint containing Cr(VI) (SCOEL 2017). In order to limit the workers’ exposure to Cr(VI) in the EU, Cr(VI) is currently regulated under both the European regulation (EC 1907/2006) on the Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) and the EU Directive 2004/37/EC on the protection of workers from the risks related to exposure to carcinogens, mutagens or reprotoxic substances at work (CMRD) (EU 2004). The current binding Occupational Exposure Limit (OEL) set under the EU Directive 2004/37/EC is 10 μg/m3 (8-h time-weighted average (8-h TWA)) until January 17, 2025. After that period, the OEL (8-h TWA) will be reduced to 5 μg/m3. For welding, plasma-cutting processes and similar work processes that generate fumes, there is a derogation with an OEL of 25 μg/m³ (8-h TWA) until January 2025; after that date the OEL (8-h TWA) of 5 μg/m3 will be applicable. France, the Netherlands and Denmark already have stricter limits, with an OEL of 1 μg/m3 (8-h TWA) for Cr(VI) in all uses (Beskæftigelsesministeriet 2020; Ministère du travail, 2012; MinSZW 2016). In the US, the American Conference of Governmental Industrial Hygienists (ACGIH) has published, for inhalable Cr(VI) compounds, a threshold limit value (TLV) of 0.2 μg/m3 (8-h TWA) and a TLV Short-Term Exposure Limit (STEL) of 0.5 μg/m3 (ACGIH 2021). No EU-wide biological limit values (BLVs) for Cr(VI) are available, however some Member States have set BLVs for occupational exposure to Cr(VI), measured as urinary chromium (U–Cr). For example, France and Finland have derived BLVs of 2.5 μg/L and 10 μg/L corresponding to their respective OELs of 1 μg/m3 and 5 μg/m3 for Cr(VI) (ANSES 2017; STM 2020). The German Research Foundation (DFG 2020) has established biological exposure equivalents for carcinogenic substances (EKA values), ranging from 12 to 40 μg/L for U–Cr. These correspond to exposures ranging between 30 and 100 μg/m3 soluble alkaline chromate and/or Cr(VI) containing welding fumes over an 8-h work shift (Bolt and Lewalter 2012). Since these current national BLVs are mainly based on studies from plating workers, they include uncertainties especially concerning their applicability to workplaces other than the electroplating industry. One of the main aims of the HBM4EU chromates study was to provide EU relevant data on the current occupational Cr(VI) exposure to support the regulatory risk assessment and decision-making process. In addition, exposure to PFASs was evaluated in a subset of workers performing chrome plating activities.This project has received funding from the European Union's Horizon 2020 research and innovation program under grant agreement No 733032 and received co-funding from the author's organizations and/or Ministries. The project team would like to thank all the companies and workers who participated in the HBM4EU chromates study and all the experts who have contributed to the conduct of the study. Participants of the HBM4EU chromates study workshop and policy questionnaires are also acknowledged. Mr. Jouko Remes and Dr. Kia Gluschkoff (Finnish Institute of Occupational Health) are acknowledged for their assistance with the statistical analyses and figures. Funding Information: This project has received funding from the European Union’s Horizon 2020 research and innovation program under grant agreement No 733032 and received co-funding from the author's organizations and/or Ministries. Publisher Copyright: © 2022 The Authors